The Effects of E‐Commerce on Regional Poverty Reduction: Evidence from China's Rural E‐Commerce Demonstration County Program. Issue 3 (25th May 2022) - Qin, Yong; Fang, Yingfeng
Abstract: This paper uses the Rural E‐Commerce Demonstration County (REDC) policy to estimate the effect of e‐commerce on poverty reduction. We discover that the REDC policy enhanced the gross regional product per capita by 8.4 percent for the total sample of counties and 10.5 percent for a subsample of poor counties. Specifically, the REDC policy increased the aggregate final product in primary industry by 10.6 percent. The final product per capita in the secondary and service sectors was 13.1 percent and 3.3 percent higher in the REDCs than in other counties, respectively. The effects were even greater for the subsample of poor counties. The estimates demonstrate that e‐commerce developed quickly in the REDCs since the implementation of the REDC policy. The income of those involved in e‐commerce increased, yielding more aggregate savings deposits. The expansion of e‐commerce induced more investment, suggesting that more aggregate loans are being made in REDCs. This evidence suggests new opportunities for poor people in the new digital economy.